The end-use quality of wheat can be enhanced by optimal water management without incurring yield loss - Sheng, Kun; Xu, Lina; Wang, Mingxia; Lei, Heng; Duan, Aiwang (Frontiers in Plant Science, 2022)
In China, water-saving irrigation is playing important roles in ensuring food security, and improving wheat quality. A barrel experiment was conducted with three winter wheat (Triticum aestivum L.) genotypes and two irrigation pattens to examine the effects of regulated deficit irrigation (RDI) on wheat grain yield, water-use efficiency (WUE), and grain quality. In order to accurately control the soil water content, wheat was planted in the iron barrels set under a rainproof shelter, and the soil water content in the iron barrel was controlled by gravity method. The mechanisms whereby water management influences the end-use functional properties of wheat grain were also investigated. The results revealed that RDI improved the end-use functional properties of wheat and WUE, without significant yield loss (less than 3%). Moderate water deficit (60% to 65% field capacity) before jointing and during the late grain-filling stage combined with a slight water deficit (65% to 70% field capacity) from jointing to booting increased grain quality and WUE. The observed non-significant reduction in wheat yield associated with RDI may be attributed to higher rate of photosynthesis during the early stage of grain development and higher rate of transfer of carbohydrates from vegetative organs to grains during the later stage. By triggering an earlier rapid transfer of nitrogen deposited in vegetative organs, RDI enhances grain nitrogen content, which in turn could enhance dough elasticity, given the positive correlation between grain nitrogen content and dough midline peak value. Our results also indicate that the effects of RDI on grain quality are genotype dependent. Therefore, the grain end-use quality of some specific wheat genotypes may be enhanced without incurring yield loss by an optimal water management.